Heterogeneous Computing: Here to Stay. - ZAHRAN, MOHAMED (Communications of the ACM, 2017)
In this article, the author reflects upon the notion of heterogeneous computing. Topics discussed include an explanation of heterogeneous computing, hardware and software challenges related to computing, and related articles on the topic including "Computing without Processors," by Satnam Singh and "A Conversation with John Hennessy and David Patterson."